Leveraging developing economies with the use of information technology trends and tools - Usoro, Abel.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book moves toward filling the gap in research on ICT and developing nations, bringing these countries one step closer to advancement through technology"--Provided by publisher.
Information technology and economic issues -- Bridging the digital divide : leveraging early strides in Nigeria / Iwara Arikpo, Adenike Osofisan, Abel Usoro -- Digital divide and disadvantaged populations in e-tourism / Billy Yfantis, Abel Usoro, Dimitris Tseles -- KNOWREM : formal definitions and ontological framework for knowledge reconciliation in economic intelligence / Adenike Osofisan -- A conceptual view of knowledge management adoption in hospitality industry of developing economies / Abel Usoro, Bridget Abiagam -- Web service composition, optimization and the implications for developing economies / Adenike Osofisan ... [et al.] -- Information technology and social issues -- Assessing the role and function of IT/IS training, development and policy implementation in a public sector organization / Nwachukwu Prince Ololube ... [et al.] -- The influence of national IT policies, socio-economic factors, and national culture on network readiness in Africa / Airi Ifinedo, Princely Ifinedo -- An empirical study of career orientations and turnover intentions of information systems personnel in Botswana / K. V. Mgaya ... [et al.] -- E-commerce trends in developing economies -- E-commerce adoption in Nigerian businesses : an analysis using the technology-organization-environmental framework / Uyinomen O. Ekong ... [et al.] -- An empirical evaluation of the effects of gender differences and self-efficacy in the adoption of e-banking in Nigeria : a modified technology acceptance model / Charles K. Ayo ... [et al.] -- Enhancing trust in e-commerce in developing IT environments : a feedback-based perspective / Iwara Arikpo, Adenike Osofisan, Idongesit E. Eteng -- Building a conceptual model of factors affecting personal credit and insolvency in China based on the methodologies used in western economies / Grzegorz Majewski, Abel Usoro, Pattarin Chumnumpan -- Using information technology to support education in developing economies : investigating e-library and e-learning -- Integrating information communication technologies (ICT) with information literacy and library-use-instructions in Nigerian universities / Aniebiet I. Ntui, Eno J. Ottong, Abel Usoro -- E-learning in higher education : the Nigerian universities' experience / Abel Usoro, Rosemary C. Akuchie -- The issues of digital natives and tourists : empirical investigation of the level of IT/IS usage between university students and faculty members in a developing economy / Nwachukwu Prince Ololube ... [et al.].
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed April 22, 2012).
Keywords: Technological innovations -- Economic aspects -- Developing countries; Community networking and information systems; Digital divide and developing countries; Distance education and e-learning; E-business and e-commerce; E-government; E-tourism; Global information systems; IT research and theory; Knowledge management; Software engineering; Electronic books